The Social and Economic Factors Influence upon the Healthcare Services Consumers Behaviour - GÂRDAN, Daniel Adrian; GÂRDAN (GEANGU), Iuliana Petronela (Annals of Spiru Haret University. Economic Series, 2015)
The research in the field of healthcare services consumer behaviour represents a very complex task with multiple implications. The consumer behaviour is much nuanced depending on the type of services or products that we are referring on. In the case of healthcare services, the behaviour is more complex than other services and is influenced mainly by special motivations like the need for a proper health status or the need to recover from a certain disease. The present article is proposing a qualitative type research as an in-depth interview with dentists regarding their perception about the influence that social and economic factors can have upon the consumers’ behaviour. The results of the research suggest that the influence of social factors is very complex, from the simple more intense concern related with dental hygiene and appearance of teeth up to anxious behaviour and isolation in the case of patients with severe dental diseases that have affected their face bones structure or the capacity to chew and speak. These findings shows that the consumers’ behaviour can be shaped by the complex interaction of different factors, and the response from dentists and those in charge with the provision of dental healthcare services can make the difference between a sustainable consumption and a dramatic route of unsatisfied consumers’ expectations.